Efeito da sequência de mistura no comportamento mecânico, térmico e reológico de blendas de PP/SEBS e PP/SEBS-MA modificadas com argila organofílica - Lima, Tiago Nunes (2021)
The improvements in the toughness of polypropylene (PP) without loss of rigidity and mechanical resistance, the addition of elastomers (SEBS) in conjunction with small amounts of clay is gaining prominence. Due to the incompatibility between these components, researchers have been indicating the addition of coupling agents, such as maleic anhydride (AM), in the polymeric matrix or in the dispersed phase and the organophilization of clays to improve the its interaction with the polymers. In addition, another approach that has been highlighted in polymeric nanocomposites is the manipulation of the morphology through changes in the sequence of addition of components with effect on several properties of the mixture. However, studies that evaluate the effect of different mixing sequences in nanocomposites of PP, SEBS pure and grafted with AM and organophilized montmorillonite clay (OMMT) are still incipient. This work aims to evaluate the effect of different mixing sequences on the mechanical, thermal and rheological properties of the PP-20%SEBS nanocomposites (pure and grafted with maleic anhydride)-5%OMMT. Through tensile and Izod impact tests, it was identified that the condition that presented the best set of mechanical properties was the mixture where clay was first added to SEBS, and this concentrate was then mixed with PP. This is due to the smaller dispersed phase size, higher crystallinity and higher clay dispersion in the morphology of this nanocomposite. The lowest mechanical properties were found in the nanocomposite in which PP, SEBS-g-MA and OMMT were mixed at the same time in the extruder, which was soon associated with coarser dispersed phase morphology, lower crystallinity and low clay dispersion in the mixture. Nanocomposites without maleic anhydride showed predominantly interlaced morphology, which favored the crystallization of these materials, resulting in higher mechanical properties. While the nanocomposites with maleic anhydride in SEBS showed predominantly exfoliated morphology and lower crystallization values, which resulted in lower mechanical properties.